An Early Abdominal Wall Ectopic Pregnancy Successfully Treated with Ultrasound Guided Intralesional Methotrexate: A Case Report - Paynesha M. Anderson; Erin K. Opfer; Jeanne M. Busch; Everett F. Magann (Obstetrics and Gynecology International)
Background. The upper anterior abdominal wall is a very unusual location for an ectopic pregnancy making optimal management uncertain. Case. We report the case of a 26-year-old gravida 4, para 1, aborta 2 with a rising quantitative human chorionic gonadotropin level following a negative diagnostic laparoscopic examination. She was subsequently diagnosed with an abdominal wall ectopic pregnancy 2 cm inferior to the liver. A single percutaneous intralesional injection of methotrexate was successful after initial failure with systemic methotrexate. Conclusion. Systemic methotrexate is a logical first choice for management of a stable early abdominal wall pregnancy. Direct intralesional injection of methotrexate as the next treatment choice may avoid the morbidity linked with operative management.